2016
DOI: 10.1128/jvi.02105-15
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Conserved Amino Terminus of the Extracellular Domain of Matrix Protein 2 of Influenza A Virus Gripped by an Antibody

Abstract: c; Structural Biology Brussels, Vrije Universiteit Brussel, Brussels, Belgium dWe report the crystal structure of the M2 ectodomain (M2e) in complex with a monoclonal antibody that binds the amino terminus of M2. M2e extends into the antibody binding site to form an N-terminal ␤-turn near the bottom of the paratope. This M2e folding differs significantly from that of M2e in complex with an antibody that binds another part of M2e. This suggests that M2e can adopt at least two conformations that can elicit prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…In DMPC bilayers, some residues show a β-strand conformation that shifts to an α-helical conformation in the presence of cholesterol (mimicking the viral membrane) [ 74 , 75 ]. It is worthwhile to mention that crystallography of M2 ED—Fab complex also suggested that M2-ED exists in different conformations supporting the notion that M2-ED is intrinsically disordered [ 76 , 77 ]. The post-APH CT up to residue 71 is largely unstructured with random coil conformation, highly mobile and, unlike the ED, insensitive to the membrane composition [ 75 , 78 ].…”
Section: Structure and Function Of The M2 Ion Channelmentioning
confidence: 87%
“…In DMPC bilayers, some residues show a β-strand conformation that shifts to an α-helical conformation in the presence of cholesterol (mimicking the viral membrane) [ 74 , 75 ]. It is worthwhile to mention that crystallography of M2 ED—Fab complex also suggested that M2-ED exists in different conformations supporting the notion that M2-ED is intrinsically disordered [ 76 , 77 ]. The post-APH CT up to residue 71 is largely unstructured with random coil conformation, highly mobile and, unlike the ED, insensitive to the membrane composition [ 75 , 78 ].…”
Section: Structure and Function Of The M2 Ion Channelmentioning
confidence: 87%
“…Earlier we reported the crystal structures of M2e in complex with the Fab fragment of two different mouse monoclonal antibodies (MAb 65 and MAb 148) that recognize partially overlapping epitopes of M2e (50,58). In these two crystal structures, M2e adopted two different conformations.…”
Section: Discussionmentioning
confidence: 99%
“…10 Interestingly, a B-cell epitope in M2e includes this range of aa 7-17, but it appears that differences in aa at certain positions 13, 14, or 18 between different strains do not markedly affect the protective efficacy of M2e immunization, whereas mutations in aa 10, 11, or 16 reduce the antibody-binding affinity. [85][86][87] Considering that M2e-specific CD4 T cells are also protective, some earlier attempts at correlating protective efficacy following M2e immunization to antibody-binding specificities exclusively may have to be revisited. A recently published report from the World Health Organization Product Development for Vaccines Advisory Committee identified 41 universal influenza vaccine candidates at various stages of development; a list that includes our own CTA1-3M2e-DD.…”
Section: Discussionmentioning
confidence: 99%
“…A tetrameric M2e vaccine formulation has been found to enhance anti-M2e antibody responses, but it would not necessarily be required for the generation of protective memory CD4 T cells, for which a less sophisticated vaccine based on peptides or monomers would be sufficient. [85][86][87] The CTA1-DD adjuvant has previously been shown to be non-toxic in mice and monkeys, it does not drive inflammation at the site of application and, importantly, it does not bind GM1-ganglioside receptors or accumulate in the central nervous tissues following i.n. administration as cholera toxin and other holotoxin adjuvants do.…”
Section: Discussionmentioning
confidence: 99%